2022
DOI: 10.1136/jim-2021-001992
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptomatology in Adults during the COVID-19 Pandemic

Abstract: Depression entails changes in the mental health of individuals worldwide. Episodes of depression lead to mood swings and changes in the motivational dimension. Our research focused on the prevalence of depression in the adult population and on how it affected the social and affective dimensions. Owing to the current pandemic, we deemed it necessary to explore how protective measures against COVID-19 infection, such as quarantines, could be related to mental health. Moreover, we found it important to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
2
2
0
Order By: Relevance
“…Thus, it was shown that particularly girls and individuals with a depressive disorder are at an increased risk of suffering from pandemic-associated psychological distress [ 58 ]. A similar pattern was observed with students (18–29 years) in Columbia after social isolation in the COVID-19 pandemic, where women exhibited a higher risk of developing depression symptoms than men [ 59 ]. Furthermore, childless people and individuals with low income were more likely to display symptoms of depression [ 59 ].…”
Section: Covid-19 and Depressionsupporting
confidence: 71%
See 1 more Smart Citation
“…Thus, it was shown that particularly girls and individuals with a depressive disorder are at an increased risk of suffering from pandemic-associated psychological distress [ 58 ]. A similar pattern was observed with students (18–29 years) in Columbia after social isolation in the COVID-19 pandemic, where women exhibited a higher risk of developing depression symptoms than men [ 59 ]. Furthermore, childless people and individuals with low income were more likely to display symptoms of depression [ 59 ].…”
Section: Covid-19 and Depressionsupporting
confidence: 71%
“…A similar pattern was observed with students (18–29 years) in Columbia after social isolation in the COVID-19 pandemic, where women exhibited a higher risk of developing depression symptoms than men [ 59 ]. Furthermore, childless people and individuals with low income were more likely to display symptoms of depression [ 59 ]. Another study among university students in Germany showed that during the pandemic (June 2020), a small increase in depression was observed, whereas anxiety and somatic complaints did not change significantly compared to before the pandemic (June–August 2019) [ 60 ].…”
Section: Covid-19 and Depressionsupporting
confidence: 71%
“…The COVID-19 pandemic has exacerbated mental health issues in the Philippines, with the National Mental Health Center reporting a spike in calls relating to mental health crises (Department of Health, 2020). Even before the pandemic, the country had one of the highest cases of depression in Southeast Asia, with females, less-educated individuals, the non-married, children, and adolescents considered the most vulnerable groups (Cuevas, 2020, as cited in Vera, 2020) (13).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to this study, 18% of the participants reported living with a mental health disorder, or that someone in their family was diagnosed with a mental health disorder in the previous six months to the survey; women and individuals aged 18 to 29 were more affected by mental disorders in comparison with men and people from other age groups. Other researchers have also identified that women, young and poor people are more vulnerable to mental health disorders (20,21). In addition, PSY-COVID-19, a study conducted in 30 countries using Patient Health Questionnaire-2 and Generalized Anxiety Disorder-2 instruments, found that 35% of respondents have a higher risk of depression, and 29% have a higher risk of anxiety (22); this percentage is lower compared to the one found by Colombia´s National Planning Department, where 52% of households reported a deterioration in mental health in adult members (23).…”
Section: Introductionmentioning
confidence: 99%